Effect of seaweed saps on growth and yield improvement of transplanted rice in old alluvial soil of West Bengal (Bangladesh Journal of Botany, 2014)
On summer rice, foliar spray was applied thrice at different concentrations (0, 2.5, 5.0, 7.5, 10.0 and 15.0%, v/v) of seaweed extracts (namely, Kappaphycus sp. and Gracilaria sp.) along with the recommended dose of fertilizer (RDF). The highest grain yield was recorded with the applications of 15% Kappaphykus sap + RDF, followed by 15% Gracilaria sap + RDF extract resulting in 41.47 and 34.99% increases, respectively compared to the control. The maximum straw yield was also achieved with 15% seaweed extract application. Improved nutrient uptake (N, P and K) was also observed with seaweed extract applications. DOI: http://dx.doi.org/10.3329/bjb.v43i1.19746 Bangladesh J. Bot. 43(1): 53-58, 2014 (June)